2008
DOI: 10.1089/sur.2007.061
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Antibacterial Efficacy of PDS Plus (Polidioxanone with Triclosan) Suture

Abstract: Polydioxanone suture with triclosan had activity in vitro against S. aureus, MRSA, E. coli, S. epidermidis, MRSE, and K. pneumoniae that persisted for as long as three weeks. In animal models, polydioxanone suture with triclosan inhibited in vivo colonization by S. aureus and E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 14 publications
2
60
0
4
Order By: Relevance
“…(25,26) Recent studies have shown that surgical site infections can be reduced through the use of sutures that have been impregnated with antibiotics. (27)(28)(29)(30) The present study was not without limitations. Due to the fact that it was a retrospective study, it may have been subject to selection bias.…”
Section: Discussionmentioning
confidence: 85%
“…(25,26) Recent studies have shown that surgical site infections can be reduced through the use of sutures that have been impregnated with antibiotics. (27)(28)(29)(30) The present study was not without limitations. Due to the fact that it was a retrospective study, it may have been subject to selection bias.…”
Section: Discussionmentioning
confidence: 85%
“…15 Triclosan coating has shown effectiveness in vitro against strains of Staphylococcus aureus, Staphylococcus epidermidis, MRSA, methicillin-resistant Staphylococcus epidermidis (MRSE), vancomycin-resistant Enterococcus faecalis, Pseudomonas aeruginosa, and Escherichia coli 16,17 and has proven beneficial in animal models (rat and guinea pig). 7,[18][19][20] Recently, a new suture material has emerged on the market that is characterized by barbs projecting from a monofilament base. To our knowledge, three different barbed sutures are currently on the market: Quill TM (Surgical Specialties Corporation), V-loc TM (Covidien), and Stratafix TM (Ethicon).…”
mentioning
confidence: 99%
“…на мировом рынке шовных материалов широко позиционируются нити, содержащие антисептик триклозан [6,14]. в исследованиях «in vitro» и «in vivo» доказано их достаточно выраженное и пролонгированное действие на широкий спектр микроорганизмов [15]. не менее эффективным представляется использование биологически активных нитей с антибиотиками [5] действием: антибактериальным и стимулирую-щим регенеративные процессы [12].…”
Section: Discussionunclassified